Sistem Informasi Pelayanan Pendaftaran Lelang Berbasis Web Pada BRI Kantor Cabang Abunjani Sipin Kota Jambi - Kesuma Wiradana, Teguh; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2023)
The web-based auction registration service system at BRI Branch Office Abunjani Sipin Jambi City is one of the state-owned banks that serves banking matters. The registration service process in data collection at the BRI Abunjani Sipin Branch Office is currently still being recorded by officers. The method used in this study is a prototype method, this study aims to analyze and design an information system for auction registration services at BRI Abunjani Sipin Branch Office Jambi City. The design of this information system produces a prototype using the Unified Modeling Language programming language, the information system that is designed can facilitate the process of inputting auction registration data where the data will be stored in the same database so that the data from the auction reports can be well integrated with each other.